A Response Analysis of Mobile Augmented Reality Application for Tourism Objects - Imam Tahyudin; Dhanar Intan Surya Saputra (International Journal of Electrical and Computer Engineering (IJECE), 2017)
As a form of innovation in a promotion media Tourism Objects in Indonesia especially at Purbalingga District, one is through Mobile Augmented Reality (MAR). The utilization of technology application of MAR, give the impression of interactive and real towards an object tourism and provide a special experience for tourists to get the information completely including the tourism location. To deliver care facilities to users, we need the evaluation to development or improvement for next application. The method used in this research is evaluation of user satisfaction towards the multimedia elements. The result of MAR user satisfaction showed that almost all respondents are well satisfied.